HIV management – an eight year experience at the Liverpool women's hospital. (18th April 2012) - Tildesley, R; Simcox, L; Topping, J
Abstract : It is estimated that approximately 83, 000 people in the UK are HIV positive and of those over 30% are unaware of their infection. In 1999 guidelines were introduced to offer antenatal HIV testing to all women, with the aim to prevent vertical HIV transmission. We retrospectively audited the care of all HIV positive pregnant patients at our Trust between 2003 & 2011, and describe the age, ethnicity, awareness of diagnosis prior to pregnancy, mode of delivery, response to HAART, complications and the neonatal outcomes over this period. Over 90% of the patient were from Sub-Saharan Africa and over 50% had acquired the infection when resident abroad. The viral load of patients at booking who were not aware of their diagnosis ranged from 4, 100 up to 570, 000. We report a single case of vertical transmission, associated with poor maternal engagement with services antenatally, and several complications including two cases of toxoplasmosis, a case of trisomy 21, and an intrauterine death associated with severe hypertension. We also describe the change in pattern of care, with a shift towards vaginal deliveries with undetectable viral loads in those patients successfully managed with HAART. Our findings reflect those in other parts of the UK, such as London with 70% of patients achieving undetectable viral loads at delivery. This, in light of the new nice guidelines, suggests that most women can achieve vaginal birth.